The story of Prophet Adam - Khan,saniyasnain (china goodwordbooks, 2021)
The story of Prophet Adam, as told by Saniyasnain Khan, focuses on his creation, the test in the Garden of Eden, and his eventual repentance and role as the first human and prophet on Earth. It emphasizes themes of obedience, the consequences of disobedience, and the importance of seeking forgiveness. The story highlights Adam's creation from clay, his knowledge, and the angelic prostration to him, as well as his and Eve's expulsion from the Garden after succumbing to temptation.